The humanism of Doctor Who a critical study in science fiction and philosophy - Layton, David (McFarland & Co., Inc., Publishers, 2012)
"From 1963 to 1989, the BBC television program Doctor Who followed a time-traveling human-like alien called "The Doctor" as he sought to help people, save civilizations and right wrongs. Though created as a family program, the series has dramatized serious themes in philosophy, science, religion, and politics"--Provided by publisher.